Transforming Library Services for Computational Research with Text Data. - Megan Senseney; Eleanor Dickson-Koehl; Beth Sandore Namachchivaya; Bertram Ludaescher (Association of College & Research Libraries, 2021)
This report from the IMLS National Forum on Data Mining Research Using In-Copyright and Limited-Access Text Datasets seeks to build a shared understanding of the issues and challenges associated with the legal and socio-technical logistics of conducting computational research with text data. It captures preparatory activities leading up to the forum and its outcomes to (1) provide academic librarians with a set of recommendations for action and (2) establish a research agenda for the LIS community.